Alterations of serum macro-minerals and trace elements are associated with major depressive disorder: a case-control study - Islam, Md Rabiul; Islam, Md Reazul; Shalahuddin Qusar, M. M. A.; Islam, Mohammad Safiqul; Kabir, Md Humayun; Mustafizur Rahman, G. K. M.; Islam, Md Saiful; Hasnat, Abul (BMC psychiatry, 2018)
Major depressive disorder (MDD) is a mixed disorder with the highly irregular course, inconsistent response to treatment and has no well-known mechanism for the pathophysiology. Major causes of depression are genetic, neurobiological, and environmental. However, over the past few years, altered serum levels of macro-minerals (MM) and trace elements (TE) have been recognized as major causative factors to the pathogenesis of many mental disorders. The purpose of this study was to determine the serum levels of MM (calcium and magnesium) and TE (copper, iron, manganese, selenium, and zinc) in MDD patients and find out their associations with depression risk. This prospective case-control study recruited 247 patients and 248 healthy volunteers matched by age and sex. The serum levels of MM and TE were analyzed by atomic absorption spectroscopy (AAS). Statistical analysis was performed with independent sample t-tests and Pearson's correlation test. We found significantly decreased concentrations of calcium and magnesium, iron, manganese, selenium, and zinc in MDD patients compared with control subjects (p < 0.05). But the concentration of copper was significantly increased in the patients than control subjects (p < 0.05). Data obtained from different inter-element relations in MDD patients and control subjects strongly suggest that there is a disturbance in the element homeostasis. Our study suggests that altered serum concentrations of MM and TE are major contributing factors for the pathogenesis of MDD. Alterations of these elements in serum levels of MDD patients arise independently and they may provide a prognostic tool for the assessment of depression risk.